Assessing Model of Tax Evasion and Firm’s Value: Moderating Role of Corporate Governance and Company Characteristics - Kautsar Riza Salman; Entis Sutisna; Halimatus Sa’diyah (Journal of Economics, Business, and Accountancy Ventura, 2024)
This study aims to examine the effect of tax evasion and corporate governance on firm value. This model uses governance and company characteristics as moderating variables of the relationship between tax evasion and firm value. This study uses panel data consisting of 18 companies in the mining sector from 2016 to 2020. The approach used is panel data using Eviews 12. This research proves that tax evasion does not have a significant direct effect on firm value. This research finds that family management and ownership concentration have a significant influence on firm value. Family management has a direct negative impact on firm value. Ownership concentration and leverage have a direct positive effect on firm value. Return on assets and company size do not have a significant influence on firm value. Governance and company characteristics are found not to moderate the relationship between tax evasion and firm value. This research presents an initial study that focuses on the relationship between tax evasion efforts and firm value in mining companies, using six analyzed models.